2022
DOI: 10.1155/2022/4801037
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Clinical Characteristics and Gene Mutation Analysis of Poststroke Epilepsy

Abstract: Epilepsy is one of the most common brain disorders worldwide. Poststroke epilepsy (PSE) affects functional retrieval after stroke and brings considerable social values. A stroke occurs when the blood circulation to the brain fails, causing speech difficulties, memory loss, and paralysis. An electroencephalogram (EEG) is a tool that may detect anomalies in brain electrical activity, including those induced by a stroke. Using EEG data to determine the electrical action in the brains of stroke patients is an effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A deep learning model was developed for real-time decoding of MEG signals, which was applied to a brain-computer interface system for regulating motor imagery tasks [96]. Epilepsy is a chronic brain disorder in which functional changes may precede structural ones and which may be detectable using existing modalities [97]. Functional connectivity analysis using EEG and resting state-functional magnetic resonance imaging (rs-fMRI) can localize epilepsy [98,99].…”
Section: Deep Learning Assisted Eeg/megmentioning
confidence: 99%
“…A deep learning model was developed for real-time decoding of MEG signals, which was applied to a brain-computer interface system for regulating motor imagery tasks [96]. Epilepsy is a chronic brain disorder in which functional changes may precede structural ones and which may be detectable using existing modalities [97]. Functional connectivity analysis using EEG and resting state-functional magnetic resonance imaging (rs-fMRI) can localize epilepsy [98,99].…”
Section: Deep Learning Assisted Eeg/megmentioning
confidence: 99%
“…The model architecture was designed to detect complex nonlinear relationships between SNV and the image data. In epilepsy, Shen et al [22], used a convolutional neural network (CNN) to predict post-stroke epilepsy. The model inputs include EEG signal data and the frequency of gene mutations in genes associated with stroke.…”
Section: Multimodal Data Integrationmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%